THE REAL ESTATE BOOM IN INDIA: IS IT A BLUNDER IN DISGUISE? - Khanna, Ridhima (2008)
This dissertation aims to evaluate the theory of Real Estate Bubbles, its consequences and policies needed to minimise its affects on the economy as a whole. Uncertainty in a market regarding the prices of an asset can lead to bubbles. Bubbles are hence understood as the instability in the asset prices due to the misinterpretation of the fundamental values of an asset which is separate from its actual market value. Different factors have been explained for this uncertainty such as principal agency problems, financial liberalisation, banking crises and growth in domestic credit Bubbles can lead to financial fragility and instability in the economy. In order to prevent these bubbles, identifying these becomes a crucial step. Hence, one need to calculate various factors developed by the economists and comprehends from the relationship between fundamentals, stock market and asset prices in order to identify the occurrence of a bubble. Once these bubbles have been identified the economists would try to control these or minimise their consequences through recapitalisation, changing of monetary and fiscal policies and restoring capital ratios. This literature on real estate bubble has then been used to understand the sudden boom in the real estate prices in India and its sudden slow down. Having understood the boom-bust cycle in various countries and carefully viewing their trends that have faced such irrational exuberance we are able to predict the future of the real estate market in India.